TAHAP PERKEMBANGAN ANAK - Pratama, Nanda Ardios; Agustina, Eka; Amri, Muhammad Syaiful; Utami, Adnani Budi (Jurnal Abdikarya: Jurnal Karya Pengabdian Dosen Dan Mahasiswa, 2019)
Early childhood development does not always evolve according to the stages of his age. There are some of them who are experiencing barriers to development such as developmental delay the child's motor and language development if it does not get the stimulus optimally from the environment. This study was conducted to determine the factors that affect early childhood development. The research was conducted with cross sectional design using a quantitative approach. Study subjects a total of 29 early childhood. The subject is taken by means of simple random sampling. Interviews and observations were conducted to get primary data about variables under study. The independent Variable in this study is the characteristics and the role of the mother, characteristics and the role of the father, characteristics and role of caregivers, the characteristics and the role of peers, characteristics and the role of the means of play. The conclusion that can be drawn is that children who did not get the role of a stimulus is optimal from the mother and the means to play the risky lbih high experience a less than optimal development. Keywords: child Development, parenting, the environment.